Children neurodevelopmental disorder assessment based on electro interstitial scan technology - Nursakinah Loqman, 1993-, author 609245 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Bio-Perubatan)) - Universiti Teknologi Malaysia, 2016